Pelatihan Pengajaran Bahasa Inggris untuk Guru SMP Gugus Kadugede di SMPN 2 Subang dengan Pendekatan English as Medium of Interaction (EMI) - Solihat, Dadang; Fadhly, Fahrus Zaman; Lismaya, Lilis (Empowerment, 2023)
The ability of teaching English among English teachers still needs to be improved. The atmosphere of  English class will feel maximal when the teacher as a key factor plays its function and ability as an attractive, energetic, creative teacher and always uses English as a medium of communication in teaching. English as Medium of Interaction (EMI) is an approach in training to improve teacher skills in teaching English to junior high school teachers in the Kadugede Group. Instructor provides training with full of English so that the trainees are moved to respond in English as well. The use of English in the classroom with a percentage of only 60%: 40% will certainly have a significant positive impact in the learning process. Motivating teachers by providing concrete examples that communicating optimally in English classes must continue to be done to get effective and efficient learning outcomes. After completion of teacher training – teachers feel motivated to teach in the classroom using EMI. They felt that during the training, they had received full training in English, so they realized that in English, students were accustomed to listening and were moved and forced to speak English because learning the language was just the matter of habit.